Bringing disability experiences front stage: Research-based theatre as a teaching approach to promote inclusive health education. (August 2022) - Jarus, Tal; Mayer, Yael; Gross, Elisabeth; Cook, Christina; Bulk, Laura Yvonne; Hershler, Laen A.D.; Nichols, Jennica; Zaman, Shahbano; Belliveau, George
Abstract: Background: Despite efforts to promote inclusion of people living with disabilities in health and human service education and professions, students and clinicians living with disabilities continue to face powerful barriers, arising most notably from the stigma and negative attitudes of their peers. Increased awareness of these lived experiences are needed to affect attitudinal changes and reduce barriers to participation in those professions. To achieve this, information (stories) must be presented to learners in a way that promotes emotional engagement and highlights these issues from multiple perspectives. The following study measures the impact of a Research based Theatre play, based on the collected experiences of people living with disabilities in health and human service professions, as a teaching approach for knowledge and attitudinal change among audiences. Method: This mixed-methods study (pre and post surveys, groups and individual interviews) aimed at measuring the impact (knowledge and attitudinal change) incurred among audience members. In total, a 174 students, faculty, staff, and clinicians in health and human service professions across two major Canadian cities completed the surveys before and after witnessing the play. Of these, 20 participants also participated in follow-up interviews. Two-way repeated measures ANOVA was used to compare the pre and post surveys while thematic content analysis was used for the interviews. Results: Two main themes emerged from combined analysis of both the quantitative and qualitative data. First, quantitative data revealed a significant change in participants' attitudes towards people living with disabilities which was corroborated by interview participants who expressed more comfort in their interactions with students and clinicians living with disabilities. Second, learners also reported meaningful and statistically significant change in their knowledge about the experiences of health and human service professionals living with disabilities. Conclusions: The results of this study support applying Research-based Theatre as a teaching approach that can promote knowledge and attitudinal change among audiences and increase the inclusion and equity of people living with disabilities in health and human service education. Future research in this area might investigate Research-based Theatre's pedagogical impact using a randomized control design and measuring longer term impact.